Uzaktan Sağlık Hizmetinde emaryolla.com ve Nöroşirürji Pratiğindeki Kullanımı: Metadolojik (Nitel Araştırmalar). - AKŞAN, Özgür (Turkiye Klinikleri Journal of Medical Sciences)
Objective: emaryolla.com (sendmri.com); It is a free online consultation system that provides emergency neurosurgical based radiological magnetic resonance imaging (MRI) image evaluation services all over the world. X-ray, computed tomography, mammography, scintigraphy and other images that are Digital Imaging and Communications in Medicine (DICOM) images can all be uploaded to emaryolla.com. Currently, it is aimed to upload the most common MRI data in neurosurgery practice, as the program serves neurosurgery. Material and Methods: The total number of patient is 2,058 during between 2016 January 2021. Questionnaires were applied to 712 of them. In this questionnaire, patients were asked it about their complaints on the phone. The most loaded image is Lumbar MRI with the complaint of low back pain. The average age is 42. 354 of the patients are male and 358 of female. Response to consultation from 25 different countries. Results: emaryolla.com runs on Linux, coded with PHP. Supported by HTML5, CSS3. jQuery and Ajax libraries are used. MySQL database is used, Codeigniter structure is used in software programming. Conclusion: Help of healthcare professionals of that country to healthcare professionals of other countries in emergency situations such as war, emergency situation and online consult; it is a project that is being worked on in order to quickly review radiological data in cases. While such systems increase the speed and capacity of the treatment, they will also act as a second eye and speed up the right decision.